Contribution of Walking to School to Individual and Population Moderate-Vigorous Intensity Physical Activity: Systematic Review and Meta-Analysis - Anne Martin; Paul Kelly; Jessica Boyle; Fenella Corlett; John J. Reilly (2016)
This study estimated the contribution of walking to/from school to objectively measured daily moderate-vigorous intensity physical activity (MVPA) in individuals and populations.MEDLINE, PsycINFO and SPORTDiscus were systematically searched up to February 2015. Two reviewers independently screened titles/abstracts/full-text articles, and assessed study quality.Of 2430 records, 129 were eligible for full-text screening. Twelve studies met the inclusion criteria of reporting objectively obtained measures of MVPA (total and while walking to/from school) in children and adolescents. The weighted mean MVPA accumulated in walking to and from school was 17 min/day in primary school pupils (9 samples, n = 3422) and 13 min/day in high school pupils (4 samples, n = 2600). Pooled analysis suggested that walking to and from school contributed 23% and 36% of MVPA on schooldays in primary school age children and high school pupils, respectively. All included studies were of high methodological quality.Walking to and from school makes a meaningful contribution to individual schoolday MVPA for active commuters in western countries. Since schooldays represent only around half of all days, and prevalence of walking to school is low in many countries, the contribution of walking to school to population MVPA is probably low.